Neutrophil–Lymphocyte Ratio as a Predictor of Major Adverse Cardiac Events Among Diabetic Population: A 4-Year Follow-Up Study. (August 2013) - Azab, Basem; Chainani, Vinod; Shah, Neeraj; McGinn, Joseph T.
The neutrophil–lymphocyte ratio (NLR) is an inflammatory marker of major adverse cardiac events (MACEs) in both acute coronary syndromes and stable coronary artery disease. The use of NLR as a predictive tool for MACEs among diabetic patients has not been elucidated. An observational study included 338 diabetic patients followed at our clinic between 2007 and 2011. Patients were arranged into equal tertiles according to the 2007 NLR. The MACEs included acute myocardial infarction, coronary revascularization, and mortality. The lowest NLR tertile (NLR <1.6) had fewer MACEs compared with the highest NLR tertile (NLR >2.36; MACEs were 6 of 113 patients vs 24 of 112 patients, respectively; P < .0001). In a multivariate model, the adjusted hazard ratio of third NLR tertile compared with first NLR tertile was 2.8 (95% confidence interval 1.12-6.98, P = .027). The NLR is a significant independent predictor of MACEs in diabetic patients. Further studies with larger numbers are needed.